Giant Peritoneal Loose Body: Case Report and Review of Literature - Oom, Rodrigo (2018)
Peritoneal loose bodies are usually diagnosed incidentally. Only a few cases are documented in the literature. The pathophysiology of this condition is not fully known and its origin may possibly be related to the twisting and separation of epiploic appendages. The authors describe the case of a patient with a spherical solid lesion 6 cm in diameter, identified incidentally in the pelvic cavity of a 64 year old man. The patient underwent laparotomy and a free ovoid shaped white body was identified. Histological examination described a calcified and encapsulated mass with a steato-necrosis core. A review of all cases of giant peritoneal loose bodies described in the literature is included. Surgical excision is recommended when the giant peritoneal loose body diagnosis is uncertain or when they are symptomatic. Doctors should be aware of its existence in order to establish a proper diagnosis and treatment plan.